Peningkatan Keterampilan Berpikir Kreatif Melalui Pembelajaran Fisika Berbasis Potensi Lokal - Siti Sarah (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2018)
The development of information and communication technology in the 21st century developed so fast. Therefore, various life skills are needed to be able to keep pace with the rapid development of technology. One of them is creative thinking skills. The skill of creative thinking can be cultivated through local potential physics-based learning. This study aims to determine whether there is an increase in creative thinking skills of students who conduct local potential based learning. The research method used was quasi experiment. The instruments used were tests and observation sheets. Data analysis used quantitative and qualitative descriptive analysis. The results showed that there is an increase in creative thinking skills of students who conducted physics learning based on local potential of 0.15975 in the low category.